2014
DOI: 10.1007/s10964-014-0146-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Familial HIV/AIDS and Symptoms of Anxiety and Depression: The Mediating Effect of Bullying Victimization in a Prospective Sample of South African Children and Adolescents

Abstract: South African children and adolescents living in HIV/AIDS-affected families are at elevated risk of both symptoms of anxiety and depressive symptoms. Poverty and HIV/AIDS-related stigma are additional risk factors for these negative mental health outcomes. Community level factors, such as poverty and stigma, are difficult to change in the short term and identifying additional potentially malleable mechanisms linking familial HIV/AIDS with mental health is important from an intervention perspective. HIV/AIDS-af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…In fact, several studies have reported that there are no direct effects of AO on mental health outcomes (e.g. Boyes et al, [111]), but that AO exerts indirect effects on indices of psychological distress, sexual risk behaviors, and educational difficulties through mediators such as community violence and abuse, as well as through poverty and AIDS-related stigma [31,66]. …”
Section: Resultsmentioning
confidence: 99%
“…In fact, several studies have reported that there are no direct effects of AO on mental health outcomes (e.g. Boyes et al, [111]), but that AO exerts indirect effects on indices of psychological distress, sexual risk behaviors, and educational difficulties through mediators such as community violence and abuse, as well as through poverty and AIDS-related stigma [31,66]. …”
Section: Resultsmentioning
confidence: 99%
“…These adolescents also experience stigma by association with family members living with HIV, which can drive persistent mental health symptoms of anxiety and depression. 23 A systematic review of psychosocial interventions focusing on mental health resilience of young people affected by HIV showed that parenting and family support were important to their mental health and psychosocial adjustment. 8…”
Section: Relationship Between Hiv and Mental Health Disordersmentioning
confidence: 99%
“…The literature on violence victimization and developmental psychology suggests that child maltreatment may also be a key driver of internalized HIV stigma via reduced psychological wellbeing [ 15 , 16 ]. Longitudinal findings from multiple systematic reviews consistently suggest that over time, child abuse victimization in the form of physical, sexual, emotional abuse and bullying leads to increases in depressive symptoms [ 17 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal findings from multiple systematic reviews consistently suggest that over time, child abuse victimization in the form of physical, sexual, emotional abuse and bullying leads to increases in depressive symptoms [ 17 22 ]. Similarly, enacted HIV stigma and bullying have been shown to have enduring negative impacts on depressive symptoms among youth from families affected by AIDS, which includes both ALHIV and HIV-negative adolescents [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation